The Role of the Audit Agency (BPK) in State Financial Management to Realize Good Governance - Pramono, Agus Joko (Perpustakaan dan Penerbitan Unismuh Makassar, 2020)
This research was conducted with the aim of knowing how the role of BPK in the management of state finances to realize good governance. By using the type of research method used is qualitative research. Based on the research, it is found that the role of BPK in realizing good governance through the implementation of audits conducted by BPK has been running optimally, this is evidenced by the mechanism for implementing audits in accordance with regulations and auditing standards for state financial management. Based on the description that the role of BPK in seeking the achievement of a good government is one of the absolute elements that must be carried out in the era of implementing and improving sustainable development bureaucracy, and in order to realize the goal of the State in achieving a just, prosperous and prosperous society. In accordance with what has been described and mandated by the 1945 Constitution of the Republic of Indonesia in Article 23E, Law of the Republic of Indonesia Number 15 of 2006, Law of the Republic of Indonesia Number 28 of 1999, and Law of the Republic of Indonesia Number 17 of 2003.